2017
DOI: 10.1186/s13662-017-1363-3
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of a new nonlinear stochastic differential competition system with impulsive effect

Abstract: We propose a new stochastic competition chemostat system with saturated growth rate and impulsive toxicant input. The main purpose of this paper is to study the stochastic dynamics of a high-dimensional impulsive stochastic chemostat model and find the threshold between persistence and extinction for the impulsive stochastic chemostat system. First, we investigate the stability of the periodic solution of a deterministic impulsive chemostat model and obtain the threshold between persistence and extinction for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…It is well known that in reality the natural growth of many populations is inevitably affected by random disturbances [48][49][50][51][52][53][54]. Many population models with random interference have been investigated [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that in reality the natural growth of many populations is inevitably affected by random disturbances [48][49][50][51][52][53][54]. Many population models with random interference have been investigated [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure goes like this: when the number of species reaches a specific requirement, the harvesting strategy is implemented, otherwise the harvesting behavior is suppressed. Some other related studies can be found in [34][35][36][37][38][39] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [14] proposed a stochastic chemostat model with periodic wash-out rate and established sufficient conditions for the existence of a stochastic nontrivial positive periodic solution for the system. Lv et al [15] proposed a stochastic competition chemostat model and derived the conditions of the threshold between persistence and extinction for the corresponding deterministic model and the stochastic model, respectively. Meng et al [16] developed a stochastic chemostat model in a polluted environment and obtained the conditions of persistence and extinction for microorganism.…”
Section: Introductionmentioning
confidence: 99%